Description of Diaulota submarina sp. nov. (Coleoptera: Staphylinidae: Aleocharinae) on Korean coasts - Ahn, Kee-Jeong (Zootaxa, 2023)
Taxonomy of the intertidal Diaulota Casey is briefly reviewed and 12 species are listed including a new species. Diaulota submarina sp. nov. is described with illustrations of diagnostic characters and a revised key to the species of Diaulota is provided. The new species is remarkably similar to D. uenoi (Sawada) and indistinguishable by external morphological characters. They can be regarded as cryptic species.